Global geographical variation in elemental and arsenic species concentration in paddy rice grain identifies a close association of essential elements copper, selenium and molybdenum with cadmium - (:unkn) unknown (My University, 2023)
Despite the centrality of staple grains for human well-being, both as a source of nutrients and of toxic ions, there is little understanding of where and how elements vary, and if there are particular elements that correlate. Here, for shop bought polished (white) rice, we comprehensively characterized trace (arsenic species, cadmium, copper, iron, manganese, molybdenum, rubidium and zinc) and macro-nutrients (calcium, chlorine, potassium, phosphorus and sulphur) for grain purchased in 18 countries, across four continents, a total of 1045 samples. This was to investigate if there were any major differences between geographic location and elemental content, and to observe if there were any patterns in elemental distribution. Greatest variation in the median was observed for the non-essential rubidium (15-fold) and arsenic species (fivefold). Rubidium was the highest in the Americas, lowest in Europe, while inorganic arsenic (iAs) and dimethylarsonic acid (DMA) were low for Africa and high in the South American and European continents. The highest concentrations of cadmium were found in Asian samples, and lowest in South America, with variation within these regions. At the extremes of individual counties, China had fivefold higher concentrations than the global median, while Tanzania was fourfold lower than this value. Calcium, potassium, molybdenum and phosphorus were the highest in European and lowest in African grain, though the fold-differences were relatively low, ~ 0.2, while iron was the highest in African grain and lowest in European, Asian and South American grain, with a ~ twofold difference. Selenium was also higher in Africa versus other regions, and copper, manganese and zinc were the highest in American grain. Factor analysis showed that copper, cadmium, molybdenum, rubidium and selenium were strongly associated together, and these element's factor loadings were diametrically opposed to less tightly associated calcium, chlorine, man
Keywords: African Research